(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This research aims to investigate the ideas, contributions, and involvement of Bukhari Iskandar in Islamic education in Labuhanbatu. Using a qualitative approach, this study employed in-depth interviews with Bukhari Iskandar’s colleagues to gather relevant data. This research indicates that Bukhari Iskandar is influential in advancing Islamic education in Labuhanbatu. His innovative ideas, including a contextual approach to religious learning, information and communication technology, and character education, have brought about positive changes in teaching and learning religion. Bukhari Iskandar’s contributions are also evident in developing a comprehensive Islamic education curriculum, intensive teacher training, and the writing and publishing of quality books. The findings of this study provide a deep understanding of the efforts made by Bukhari in strengthening religious education, enhancing teaching quality, and expanding access to Islamic education in the region.